Teacher-Student Attachment And Teachers’ Attitudes Towards Work - Ahmad, Affizal; Sahak, Rafidah (Penerbit Universiti Sains Malaysia, 2009)
This study examines the relationship between teacher-student attachment and teachers’ attitude towards work. We show that teacher-student attachment and teachers’ attitudes towards work appear critical in promoting and maintaining positive teacher behaviours. Communication connects students with teachers, improving the classroom atmosphere. Teachers who communicate effectively with their students can give them appropriate and helpful feedback. Teacher-student interaction is extremely important for a successful relationship through the entire school year